Indian foreign policy challenges and opportunities - Sinha, Atish; Mohta, Madhup; Foreign Service Institute (India) (New Delhi Academic Foundation, 2007)
Contributed articles on post 1984 foreign relations issues.
At head of title: Foreign Service Institute, New Delhi.
Keywords: India -- Foreign relations -- 1984-.